Bahasa Inggris - mufrodah, alia; Adinugraha, Hendri Hermawan (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2021)
The type of skincare cosmetic product is one of the beauty products needed to support beauty and facial skin health. The need in fulfilling facial skin care is included in changes in economic behavior patterns in the millennial generation. The industry about halal cosmetics is currently experiencing a very rapid development of this because the community is currently aware of the importance of using halal products. This study aims to analyze any factor that can form a millenial generation awareness in choosing halal labeled cosmetics. The research used is descriptive qualitative research. Research with the method or case study approach. Under the Republic of Indonesia Law No. 33 of 2014, the magnificence quality of cosmetic products is determined by raw materials and production processes. Factors that are indicators of millennial generation awareness in choosing halal products are: a) Halal raw materials, b) religious obligations, c) production process, d) product hygiene, e) knowledge of international halal products.